Consuming pleasures : intellectuals and popular culture in the postwar world - Horowitz, Daniel, 1938- (Arts and intellectual life in modern America., 2012)
How is it that American intellectuals, who had for 150 years worried about the deleterious effects of affluence, more recently began to emphasize pleasure, playfulness, and symbolic exchange as the essence of a vibrant consumer culture? The New York intellectuals of the 1930s rejected any serious or analytical discussion, let alone appreciation, of popular culture, which they viewed as morally questionable. Beginning in the 1950s, however, new perspectives emerged outside and within the United States that challenged this dominant thinking. Consuming Pleasures reveals how a group of writers shifted attention from condemnation to critical appreciation, critiqued cultural hierarchies and moralistic approaches, and explored the symbolic processes by which individuals and groups communicate. Historian Daniel Horowitz traces the emergence of these new perspectives through a series of intellectual biographies. With writers and readers from the United States at the center, the story begins in Western Europe in the early 1950s and ends in the early 1970s, when American intellectuals increasingly appreciated the rich inventiveness of popular culture. Drawing on sources both familiar and newly discovered, this transnational intellectual history plays familiar works off each other in fresh ways. Among those whose work is featured are Jürgen Habermas, Roland Barthes, Umberto Eco, Walter Benjamin, C.L.R. James, David Riesman and Marshall McLuhan, Richard Hoggart, members of London's Independent Group, Stuart Hall, Paddy Whannel, Tom Wolfe, Herbert Gans, Susan Sontag, Reyner Banham, and Robert Venturi and Denise Scott Brown.